Platelet-Rich Plasma, Low-Level Laser Therapy, or Their Combination Promotes Periodontal Regeneration in Fenestration Defects: A Preliminary In Vivo Study - Nagata, Maria José Hitomi [UNESP]; Campos, Natalia de [UNESP]; Messora, Michel R.; Pola, Natalia M. [UNESP]; Santinoni, Carolina S. [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Fucini, Stephen E. [UNESP]; Ervolino, Edilson [UNESP]; Almeida, Juliano Milanezi de [UNESP]; Theodoro, Letícia Helena [UNESP]; Garcia, Valdir Gouveia [UNESP] (Amer Acad Periodontology, 2014)
Background: This study histomorphometrically analyzes the influence of platelet- rich plasma (PRP), low- level laser therapy (LLLT), or their combination on the healing of periodontal fenestration defects (PFDs) in rats.Methods: PFDs were surgically created in the mandibles of 80 rats. The animals were randomly divided into four groups: 1) C (control) and 2) PRP, defects were filled with blood clot or PRP, respectively; 3) LLLT and 4) PRP/LLLT, defects received laser irradiation, were filled with blood clot or PRP, respectively, and then irradiated again. Animals were euthanized at either 10 or 30 days post-surgery. Percentage of new bone (NB), density of newly formed bone (DNB), new cementum (NC), and extension of remaining defect (ERD) were histomorphometrically evaluated. Data were statistically analyzed (analysis of variance; Tukey test, P < 0.05).Results: At 10 days, group PRP presented ERD significantly lower than group C. At 30 days, group PRP presented NB and DNB significantly greater than group C. Groups LLLT, PRP, and PRP/LLLT showed significant NC formation at 30 days, with collagen fibers inserted obliquely or perpendicularly to the root surface. NC formation was not observed in any group C specimen.Conclusions: LLLT, PRP, or their combination all promoted NC formation with a functional periodontal ligament. The combination PRP/LLLT did not show additional positive effects compared to the use of either therapy alone.
Keywords: Laser therapy, low-level; models, animal; periodontics; platelet-rich plasma; regeneration; wounds and injuries